Experimental and mathematical analysis of a multi-layer system of railway track - Hana Hana Krejcirikova; Martin Lidmila (Communications - Scientific letters of the University of Zilina, 2004)
Based on experimental measurement of a model of a multi-layer non-linear system with inserted geosynthetic layers of the permanent way structure, a new design method will be designed for dimensioning the sleeper subgrade structure using classical and geosynthetic materials or sub-ballast vibration-damping matting. The results of measurements on a track structure model in a 1:1 scale performed in a testing box will be verified by means of a numerical model. A two-dimensional solution will be subsequently verified by means of a spatial model. Numerical modelling will serve for transferring the values measured on the experimental model into a current railway track structure.